Exogenously applied putrescine and chitosan–putrescine nanocomposite alleviate the negative effects of chilling stress on iceberg lettuce seedlings - Andrzej Kalisz; Andrzej Kornaś; Joanna Gil; Agnieszka Sękara; Dalibor Húska; Elżbieta Rudolphi-Szydło; Apolonia Sieprawska; Katarzyna Gawrońska; Muhittin Kulak; Vasileios Fotopoulos; Gholamreza Gohari (Scientific Reports)
Abstract Climate change-induced stressors such as extreme temperatures negatively affect plant growth and development. Therefore, methods are needed to improve plant tolerance to abiotic stresses. The aim of this study was to evaluate whether the foliar application of putrescine (Put) and a chitosan–putrescine nanocomposite (Ch–Put) can modulate the antioxidant response and membrane properties of lettuce under chilling stress. In this study, Put and Ch–Put were applied via foliar spraying at two concentrations (1 mM and 2.5 mM), and after treatment, the plants were placed in a phytotron at 4 °C and 20 °C. Changes in the properties of the cell membranes were assessed in the seedlings. Additionally, the antioxidant enzymatic activity and content of nonenzymatic bioactive compounds were evaluated. The results indicated that the use of Put and Ch–Put influenced the permeability and fluidity of the lipid membranes, which also depended on the treatment temperature. An increase in Alim (all treatments) and a decrease in Cs⁻1 values (Put and Ch–Put at a concentration of 2.5 mM) were observed at 4 °C, suggesting looser packing and increased elasticity of cell membranes, facilitating the metabolic and physiological adaptation of plants to stress. The treatment of chilled plants with Put and Ch–Put resulted in increased contents of proline, carbohydrates, glutathione, phenolics and L-ascorbic acid, as well as increased activity of several antioxidant enzymes, such as catalase (CAT) and ascorbate peroxidase (APX), which could contribute to increased tolerance to stress. The strongest effects were observed for Put at concentrations of 1 mM and 2.5 mM and Ch–Put at the 2.5 mM concentration, suggesting the potential use of these substances in strategies to increase plant tolerance to chilling stress.